2016
DOI: 10.1051/0004-6361/201527462
|View full text |Cite
|
Sign up to set email alerts
|

Iron-rich solar particle events measured by SOHO/ERNE during two solar cycles

Abstract: Aims. We study the differences in the heavy ion composition of solar energetic particle (SEP) events between solar cycles 23 and 24. Methods. We have surveyed the SOHO/ERNE heavy ion data from the beginning of solar cycle 23 until the end of June 2015, that is, well into the declining phase of cycle 24. We used this long observation period to study the properties of heavy ions (from C to Fe) and to compare the two solar cycles in this respect. We surveyed the data for SEP events with enhancements in the Fe/C a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The SEP ion abundances relative to hydrogen observed in SC 24 over that observed in SC 23 was proportional to (Q/M) 0.66 . Raukunen et al (2016) considered the daily intensities of the time periods with statistically significant amounts of heavy ions during the two cycles and found that the fluence distributions show the largest lack of high fluences for the low Q/M elements. Thus, elements with the lowest Q/M consistently show the largest depletion from SC 23 to 24.…”
Section: Sep Events and The Related Cmesmentioning
confidence: 99%
“…The SEP ion abundances relative to hydrogen observed in SC 24 over that observed in SC 23 was proportional to (Q/M) 0.66 . Raukunen et al (2016) considered the daily intensities of the time periods with statistically significant amounts of heavy ions during the two cycles and found that the fluence distributions show the largest lack of high fluences for the low Q/M elements. Thus, elements with the lowest Q/M consistently show the largest depletion from SC 23 to 24.…”
Section: Sep Events and The Related Cmesmentioning
confidence: 99%